1999
DOI: 10.1254/jjp.79.89
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Denaturation by Fatty Acids, Bile Salts and Other Natural Substances: A New Hypothesis for the Mechanism of Action of Fish Oil in Rheumatic Diseases

Abstract: Natural hydrophobic substances like bile salts (cholate, deoxycholate, chenodeoxycholate, lithocholate and their conjugates with glycine and taurine), fatty acids (caprylic, capric, lauric, myristic, palmitic, stearic, oleic, linoleic, arachidonic, eicosapentaenoic and docosahexaenoic acid) were much more active (EC50 approximately 10(-4)-10(-5) M) than selected amino acids (EC50 > 10(-2) M) and inorganic salts (EC50 approximately 10(-1) M) in inhibiting heat-induced denaturation of human serum albumin in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Studies on the stabilization induced by different chemical agents are of considerable importance. [14][15][16][17]21,[57][58][59] We performed a study on the stabilization effect of a NSAID, the ibuprofen. To verify the protective action of the ibuprofen, an analysis with SAXS, DLS, CD and fluorescence techniques was carried out on a set of solutions with urea concentrations between 0.00 and 9.00 M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the stabilization induced by different chemical agents are of considerable importance. [14][15][16][17]21,[57][58][59] We performed a study on the stabilization effect of a NSAID, the ibuprofen. To verify the protective action of the ibuprofen, an analysis with SAXS, DLS, CD and fluorescence techniques was carried out on a set of solutions with urea concentrations between 0.00 and 9.00 M.…”
Section: Discussionmentioning
confidence: 99%
“…Saso et al 15,16 reported the stabilization activity of numerous drugs, studying the variation of absorbance (turbidimetric method) or the aggregation (HPLC technique) of HSA:ligand solutions in heat-induced denaturation conditions. These works show that FA, NSAIDs and a surfactant, the sodium dodecyl sulfate, are the more active compounds.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Increasing the amount of EPA in membrane phospholipids not only reduces the level of arachidonic acid (AA) available for metabolism by lipoxygenases and cyclooxygenases, but also competes with AA for metabolism to form metabolites of less proinflammatory than the AA derived metabolites, thereby taming the inflammatory reaction (Calder, 2006). Long chain fatty acids have been reported to have anti-denaturant activity that protects against protein denaturation, which might be beneficial in rheumatoid arthritis and other rheumatic conditions (Saso et al, 1999). This is may be another mechanism of action of primrose oil and fish oil due to their long chain fatty acid contents.…”
Section: Discussionmentioning
confidence: 99%
“…12 Saso et al, 1999 demonstrated that presence of PUFA such as AA, LA and ALA etc. inhibit heat induced protein denaturation 13,14 Hence, it becomes essential to assess the level of protein denaturation in presence of SBT seed oil to understand its potential in chronic inflammatory conditions.…”
Section: Inhibition Of Protein Denaturationmentioning
confidence: 99%
“…Hence, membrane stabilization was taken up as a measure of the anti-inflammatory property of SBT seed oil. Chronic inflammatory conditions may involve protein denaturation.12 Saso et al, 1999 demonstrated that presence of PUFA such as AA, LA and ALA etc. inhibit heat induced protein denaturation 13,14 Hence, it becomes essential to assess the level of protein denaturation in presence of SBT seed oil to understand its potential in chronic inflammatory conditions.…”
mentioning
confidence: 99%